Comparison between Spinal and Caudal Anesthesia in Pediatric Patients at Dhaka Shishu Hospital - Hossain, Md Makbul; Iqbal, Md; Ahamed, Sabarin; Tarik, Khalifa Mahmud; Hira, Md Yousuf; Islam, Atiqul (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background: Regional anesthesia in children was first studied by August Bier in 1899. Since then,spinal anesthesia was known to be practiced for several years with a series of cases published as early asin 1909-1910. The appearance of neuromuscular blocking agents and the development of volatileanesthetics in the forties shifted the techniques toward general anesthesia. Objective: To compare the technique regarding onset of block, level of block and duration of analgesia. Material & Method: All the study patients were examined day before surgery & all routine investigationswere noted. All the patients were kept nothing by mouth for 6 hours before the surgery. Patient’s guardianor the parents were informed about anesthetic procedure and the informed consent was taken. Result & Conclusion: In the present study the effectiveness of the caudal anesthesia was comparedwith the spinal anesthesia. The dosage was taken as per mg/kg for producing adequate anesthesia asper the guidance provided in the different other studies but different authors. JBSA 2019; 32(2): 32-35